2002
DOI: 10.1046/j.1365-2745.2002.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental farming protects children against atopy: longitudinal evidence involving skin prick tests

Abstract: A farming environment has a strong negative effect on the development of allergic sensitization. Furthermore, the study provides evidence that atopic children living on a farm lose their SPT positivity more frequently than children from non-farming environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 21 publications
5
41
1
Order By: Relevance
“…Among children aged 7-8 yrs, the prevalence of atopy in the children of Cretan farmers was far higher than that among farming children in Austria [7] but not dissimilar to estimates among farming children living in Sweden, Australia or Finland [8,11,12]. Conversely, the prevalence of atopy among children of nonfarmers in Crete is consistently lower than that among similar children living in any of the other communities studied.…”
Section: Animal Locationmentioning
confidence: 58%
“…Among children aged 7-8 yrs, the prevalence of atopy in the children of Cretan farmers was far higher than that among farming children in Austria [7] but not dissimilar to estimates among farming children living in Sweden, Australia or Finland [8,11,12]. Conversely, the prevalence of atopy among children of nonfarmers in Crete is consistently lower than that among similar children living in any of the other communities studied.…”
Section: Animal Locationmentioning
confidence: 58%
“…Swiss school children showed to have atopy, measured by radioallergosorbent test, and symptoms of hay fever significantly less frequently than children from the same area who have not been growing up on a farm (114). This inverse association between exposure to farm/country environment in childhood and the subsequent development of atopic disorders has been confirmed by further studies in Germany (115), Austria (116,117), Finland (118), Denmark (119), Canada (120) and France (121) There is also some evidence to suggest that exposure to country living also in later childhood or even in adulthood 'ever living in the country' may confer protection against asthma and atopy implicating that immunomodulation may not be restricted to exposure in the first years of the life only (121). Importantly, a study from New Zealand has shown that the results obtained from Europe and Canada are not necessarily applicable to other continents and countries.…”
Section: Exposure To Farm/country Environment and Petsmentioning
confidence: 71%
“…In a Norwegian cohort study of 2,531 children followed for 4 years from birth, the risk of asthma was lower in children with any pet at birth, with an adjusted OR of 0.7 (95% CI 0.5–1.1) [21]. In particular, growing up on a farm and exposure to livestock appears to provide protection against development of atopic disease in some Western populations [22, 23]. It has been proposed that high exposure to microbial products, such as bacterial endotoxin, in the first years of life may mediate this protective effect [24, 25].…”
Section: Discussionmentioning
confidence: 99%